Logistic warehouse modern systems - Calsina Miramira, Willy Hugo (2009)
In the development of our experience in the logistics area and the research of the last applied technologies to the materials management, we allow writing this article about automated storages that are using in Europe and North America. In our country there are specialized enterprises that offer them to different industries, but their acceptation is based in the high investment which needs to purchase and implement them. It is necessary to indicate that storages reduce times and gain the aero space, so the enterprises grow with their machines, but they cannot to do growing their storages horizontally. For that reason, the enterprises use their aero space and use the technology of automated storages, which is developed in this article.